"Book Club" Guides A Working Group to Create INCOSE System‐Software Interface Products. Issue 2 (6th August 2021) - Sheard, Sarah; Bouyaud, Mickael; Osaisai, Macaulay; Siviy, Jeannine; Nidiffer, Ken
ABSTRACT: Many software‐dominant organizations ignore systems engineering completely. A recent popular book described one such organization in a fable format. The INCOSE Systems and Software Interface Working Group chose to read this book as a weekly professional development seminar to investigate where systems engineering should fit in software‐dominant organizations of the type that do not currently involve INCOSE's systems engineers. This seminar culminated in an "author day, " where the book's author responded to our questions and discussed our potential role. The book club activities produced several drafts we can turn into products to help INCOSE systems engineers better understand software, and systems engineers' potential role in such organizations, to help improve software‐intensive system success.